Inorganic nitrogen content of brown rice in some Malayan paddy varieties - Quah, S. C.; Mohan Rao, P. K. (Society for the Advancement of Breeding Researches in Asia and Oceania, 1972)
Non-protein nitrogen in brown rice is derived from free amino acids, poly- amines, nitrates, and possibly nitrites. Total amount of non-protein nitrogen was variably estimated to be around 2 per cent (Kester, Pence and Kohler 1961); .3.5 per cent (McIntyre 1956); 4 to 5 per cent (Jodidi 1920) of the total nitrogen of the rice kernels. Free amino acids were found to constitute from 0.06 to 0.68 per cent of the total nitrogen (IRRI annual report 1964). Very little is known about the exact contribution of inorganic nitrogen compounds (nitrates and nitrites) to the total nitrogen content of rice kernels. In this paper, the contri- bution of nitrate to the total nitrogen content of the rice kernels under different conditions is reported